Use of Saccharum Officinarum vinasse for stabilization of cohesive soils - Bustamante Salazar, Flor Lisbet (2025)
This article shows the use of Saccharum officinarum stillage in stabilizing cohesive soils. These soils in mention are those that present very poor resistance properties, which prevents the soil from working properly as part of a subgrade on a road. The objective of the research was to determine the stabilization of cohesive soils with the incorporation of vinasse from Saccharum officinarum. The type of research is experimental, the technique used is observation and data collection sheet, through which it was possible to obtain values from the tests carried out in the laboratory with natural soil and soil stabilized with Saccharum officinarum vinasse. The results indicate that the soil under study is low plasticity inorganic silts and clays. With the application of s Saccharum officinarum vinasse, it was identified that the density of the soil increases with the different percentages used. Then, when carrying out the mechanical resistance tests of the stabilized soil, it was possible to increase the resistance with respect to that of the natural soil, being 25% of Saccharum officinarum vinasse the one that obtained the highest values. Research concludes that the incorporation of Saccharum officinarum stillage increases the strength properties of a cohesive soil.